Improving Student’s Reading Comprehension through Question-Answer Relationship of MTs Al-Washliyah Jati Rejo, Galang District Academic Year 2019/2020 - Rahayu, Chinta; Tambusai, Azhary; Zulfitri, Zulfitri (Education & Learning, 2023)
This research is aimed at improving the reading comprehension of MTs Al-Washliyah Jati Rejo, Kec.Galang grade VIII students using QAR strategy. In conducting this study, the researcher applied Classroom Action Research (CAR) as the method of research. It was conducted in two cycles and each cycle consisted of four phases: planning, acting, observing, and reflecting. This research answered two questions (1) How is the implementation of using Question Answer Relationship (QAR) to enhance the students’ reading comprehension in the narrative text at the eight grade of MTs Al-Washliyah Jati Rejo, Kec.Galang in the academic year of 2019/2020? (2) How is the result of the use of Question-Answer Relationship (QAR) strategy in the narrative text at the eight grade of MTs Al-Washliyah Jati Rejo, Kec.Galang in the academic year of 2019/2020? In reference to the application of the two cycles, the results of the research revealed that the use of schema activation strategy successfully improved the students‘ reading comprehension. The students’ interest and attention in the process of teaching and learning English, especially reading, reading improved. They were also able to explore many words related to the topic of the lesson. In relation to their comprehension of English texts, the students were able to identify main ideas and supporting details of paragraphs correctly